Information Effects on the Bid‐Ask Spread - COPELAND, THOMAS E.; GALAI, DAN (Journal of Finance, 1983)
ABSTRACT An individual who chooses to serve as a market‐maker is assumed to optimize his position by setting a bid‐ask spread which maximizes the difference between expected revenues received from liquidity‐motivated traders and expected losses to information‐motivated traders. By characterizing the cost of supplying quotes, as writing a put and a call option to an information‐motivated trader, it is shown that the bid‐ask spread is a positive function of the price level and return variance, a negative function of measures of market activity, depth, and continuity, and negatively correlated with the degree of competition. Thus, the theory of information effects on the bid‐ask spread proposed in this paper is consistent with the empirical literature.